A DESOBEDIÊNCIA POÉTICA DE CORPOS-ANTÍGONAS: CENAS DE CORPOS QUE NÃO IMPORTAM - Bruna Franco Neto (2024)
The present work presents an investigation into the appropriation and disappropriation, in the terms of Rivera Garza (2013), by contemporary Latin America of the classical figure of Antigone. Assuming an adjectival perspective of “antigone,” the work explores new interpretative possibilities for Latin American “antigone-bodies” through performative art and literature. To this end, it is divided into two main parts. In the first, I share my experiences from artistic practices, both as an artist and as a spectator and researcher. In this exchange, I share readings based on my artistic experience in the Agora Antigone Project — Performance in Network, developed by the Cabeça de Cuia Cultural Group and Producer, from Bahia, at the beginning of the pandemic in 2020. This project invited artists to reinterpret the myth of Antigone through networked performances, emphasizing the contemporary relevance of the disobedience and resistance embodied by the character. In the reflection proposed on these performances, I bring some considerations about performance, especially through the lenses of Cohen (2002) and Zumthor (2007), with the first elucidating performance as a border-crossing, multiple art form, and the second proposing performance as an act of language endowed with corporeality. In the second part, I return to speak from the literary work that will be analyzed here: Antígona González. A Latin American work that, while it recovers the Greek mythological figure, transcends it to address the struggles from this side, bringing into its poetic-dramatic form multiple voices of many “antigone-bodies,” both fictional and non-fictional. The analytical reading of Antígona González is composed around three main points: the body, disobedience, and memory. These points are also discussed in a way that intertwines them, retrieving the performative approach introduced in the first part. The body, as read in these literary and performative works, is constructed and supported by the theories of David Lapoujade (2002), Deleuze (2002), Le Breton (2007), José Gil (1997), Butler (2019), and Henz (2012). In these works, the body is understood not only as a physical entity but also as a space of resistance, meaning-making, and memory-building. Disobedience is another fundamental aspect of the work, addressed both as a political act and as an epistemic practice. To support the discussion, theories by Frédéric Gros (2018), Judith Butler (2022), Walter Mignolo (2008), and others are introduced to demonstrate how the disobedience of these “antigone-bodies” in the analyzed works manifests as resistance to necropolitics (Mbembe, 2018) and to social, political, and cultural control. Disobedience is thus seen as a radical and poetic alternative to state violence and the hierarchy of life. Weaving throughout the writing, memory is explored as a continuous process of construction and reconstruction, mediated by art, whether literary or not, and by performance. For this purpose, a dialogue is proposed with the works of Assmann (2011), Gagnebin (2006), and Rivera Garza (2013) to argue that the literary and performative works investigated not only recover silenced memories but also create new spaces for resistance and identity. Memory, from the perspective of this work, is an act of disobedience against official history and regimes of forgetting.